Training sessions as an important condition for the formation of skills of professional self-organization for future teachers - Дуднік, Н. Ю. (Pedagogy of Higher and Secondary Education, 2012)
Dudnik N. Yu. Training sessions as an important condition for the formation of skills of professional self-organization for future teachers. The article deals with the problem of personal future teachers’ development, the skills of their professional self-organizing and the training-classes as the effective means of their formation.